Prolonged Power Outages and Air Quality: Insights from Quito’S 2023–2024 Energy Crisis - Campos-Bravo, V (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The 2023–2024 blackouts in Quito, Ecuador, led to severe air quality deterioration, primarily driven by diesel generator use and increased vehicular traffic. This study analyzed data from seven urban and peri-urban monitoring stations, applying meteorologically normalized data and machine learning models (Boosted Regression Trees and Random Forests) to isolate the direct impact of blackouts on pollutant concentrations. The results revealed that PM10 increased by up to 45% and PM2.5 by 30%, frequently exceeding regulatory limits, particularly in industrial and residential zones. SO2 exhibited the most extreme rise, surging by 390%, with peak values reaching 500 µg/m3 in areas heavily reliant on high-sulfur diesel generators. The NO2 concentrations exceeded 200 µg/m3 in high-traffic areas, while O3 showed dual behavior, decreasing in urban cores due to titration effects but increasing by 15% in suburban valleys, driven by photochemical interactions. A comparison between 2023 and 2024 blackouts highlighted worsening pollution trends, with longer (8–12 h) outages in 2024 causing severe environmental impacts. The findings demonstrate that blackouts significantly worsen air quality, posing critical public health risks. This study underscores the urgent need for policy interventions to mitigate the environmental impact of energy disruptions. Key recommendations include stricter fuel quality standards, diesel generator emission controls, and an accelerated transition to renewable energy. These results provide scientific evidence for future environmental regulations, supporting sustainable air quality management strategies to minimize future energy crises’ health and ecological consequences. © 2025 by the authors.